Pengembangan Arsitektur Sistem Informasi Multi Toko Emas pada Adil Gold Store - Purwono, Purwono; Dewa, Bala Putra (Jurnal IT UHB, 2023)
The development of information technology has an impact on the number of information systems in various fields as a form of implementing technological needs in the digital era. Gold shop is one type of business that requires an information system because there are still many transaction processes that are processed manually so that errors occur in the reports. Adil Gold Store is one of the largest gold shops in Banyumas Regency, which has 6 main branches, namely Wangon, Ajibarang, Cilongok, Pemalang, Jatilawang and Cilacap. Adil Gold Store requires an information system with centralized data, meaning that both buying and selling of gold can be monitored in one application by the owner. Management of product stock and inventory is also still manual which is ineffective. The additional innovation needed is the need for a mobile application for members. Based on these needs, an information system was created using the prototype method. This is because the gold shop is a very complex system and requires more in-depth analysis. The result of developing this system is a gold shop website equipped with a mobile application for members. The results of system testing show that performance is considered quite good because the testing accuracy of each role is above 90%, but some system errors still need to be fixed so that they can actually run properly